Ruptured heterotopic pregnancy with successful term intrauterine pregnancy outcome after natural conception: a case report - Hassen Mohammed Areys; Mahamed Sheikahmed Abdi; Nour Hies Omer; Osman Ali Osman; Tariku Mulatu Bore (Journal of Medical Case Reports)
Abstract Background Heterotopic pregnancy is the simultaneous existence of intrauterine and extrauterine pregnancies. This is a rare obstetric case, with an incidence of 1 in 30,000 in naturally conceived pregnancies and 1 in 100 pregnancies achieved through in vitro fertilization. Early diagnosis of heterotopic pregnancy is challenging in developing countries with no high-resolution ultrasound. Case presentation A 22-year-old multigravida Somali mother presented to our hospital on her tenth week of gestation with the complaint of progressively worsening abdominal pain of 7 days’ duration. The patient had type III female genital mutilation at the age of 7 years. The patient presented with tachycardia, but her overall hemodynamic status remained stable. Obstetric ultrasound showed a right-sided adnexal mass, a hemoperitoneum, and an intrauterine pregnancy at 10 weeks + 2 days of gestation. Two units of screened, cross-matched whole blood were prepared, and the patient underwent an exploratory laparotomy. Intraoperative findings revealed a right-sided ruptured tubal ectopic pregnancy at the ampulla with active bleeding, a hemoperitoneum of approximately 900 mL with clots, and a bulky uterus about 10 weeks in size with a normal left tube and ovary. The patient had a brisk recovery postoperatively, and the intrauterine pregnancy was conservatively monitored until term gestation. An alive female neonate weighing 3000 gm was delivered via spontaneous vertex delivery with an Apgar score of 8 and 9 in the first and fifth minutes, respectively. Conclusion Heterotopic pregnancy is a rare obstetric condition that can occur through natural conception. Female genital mutilation might be an independent risk factor for heterotopic pregnancy that occurs via natural conception. The presence of an intrauterine gestation does not rule out a concomitant extrauterine gestation, so a high index of suspicion and timely diagnosis should be made for a pregnant woman presenting with acute abdominal pain and an adnexal mass. A routine early-first-trimester antenatal ultrasound scan of the adnexa by an experienced obstetrician or sonographer is paramount to obtaining an accurate and timely diagnosis.